1990
DOI: 10.1002/eji.1830200221
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antigen‐specific CD4+ HLA‐DR‐restricted cytotoxic T lymphocytes as well as nonspecific nonrestricted killer cells by the recombinant mycobacterial 65‐kDa heat‐shock protein

Abstract: Acquired cell-mediated immunity to intracellular parasites like mycobacteria is dependent on antigen-specific T lymphocytes. We have recently found that mycobacteria not only induce helper T cells but also cytotoxic CD4+ and/or CD8+ T cells as well as nonspecific killer cells that lyse human macrophages in vitro. In addition, we have described that the recombinant heat-shock protein (hsp) 65 of Mycobacterium bovis BCG/M, tuberculosis is an important target antigen for CD4+CD8- cytotoxic T cells. We have now fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 43 publications
2
23
1
Order By: Relevance
“…On the other hand, 16/20 MB patients were unable to develop specific cytotoxic T cells; only those patients undergoing an ENL episode elicited cytotoxic responses against hsp65-pulsed macrophages (Table 3). Our results thus further confirm and extend the findings of Kale Ab et al [14] that Myco. leprae hsp65 does not trigger cytotoxic effector cells in most MB patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, 16/20 MB patients were unable to develop specific cytotoxic T cells; only those patients undergoing an ENL episode elicited cytotoxic responses against hsp65-pulsed macrophages (Table 3). Our results thus further confirm and extend the findings of Kale Ab et al [14] that Myco. leprae hsp65 does not trigger cytotoxic effector cells in most MB patients.…”
Section: Discussionsupporting
confidence: 93%
“…leprae recombinant proteins [11][12][13] and induction of cytotoxic T lymphocytes by the recombinant 65-kD heat shock protein (hsp65) of Myco. bovis BCG have been demonstrated [14][15][16]. These cytotoxic T lymphocytes react with macrophages pulsed with BCG-hsp or Myco.…”
Section: Introductionmentioning
confidence: 99%
“…Although mycobacteria induce preferentially CD4 CTL [16,21], we [8] as well as others [5] have demonstrated that both CD4 and CD8 cytotoxic effector cells can be generated from PBMC. An important role has been recently suggested for class I-restricted CD8 T cells in TB [22].…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have suggested that CTL could play an important role in the immune response to mycobacterial infections such as leprosy and tuberculosis (TB) [5,7,16]. In a previous work we have demonstrated that M. leprae hsp65 could induce cytotoxic effector T cells from PBMC of PB patients and normal controls; in MB patients a marked deficiency in developing hsp65-specific CTL activity was found [10].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation